FRI0221 Salivary cystatin C and the imbalance between cysteine proteases and their inhibitors in churg strauss syndrome. (23rd January 2014) - Martini, D.; Baldini, C.; Latorre, M.; Giorgerini, V.; Carnicelli, V.; Sabbatini, A.; Tavoni, A.; Bombardieri, S.
Abstract : Background: Cystain C is a major constitutive secretory product of alveolar macrophages and a potent regulator involved in the remodeling associated with lung inflammatory processes. Debatable data have been reported on serum Cystatin C levels in asthmatic patients. Recently, serum Cystatin C has been also associated with small vessel vasculitis such as Henoch Schonlein purpura and Kawasaki disease. No data are available on Cystatin C and Churg Strauss syndrome, a challenging small vessel vasculitis which combines both vascular inflammatory damage and asthma. Objectives: i) To investigate salivary expression of Cystatin C in consecutive patients with CSS in comparison to healthy volunteers focusing in particular the eventual correlations between Cystatin C and asthma severity and airway inflammation ii) to compare Cystatin C levels with the expression of the other members of cystatin family (cystatin S, SA and SN) in the whole saliva of the subjects enrolled in order to explore the salivary balance between cysteine proteases and their inhibitors in CSS patients. Methods: Consecutive patients with a diagnosis of CSS (ACR criteria) and sex and age matched healthy volunteers were enrolled in the study. Asthma severity was evaluated according to FEV1, FEV1/SVC, GINA guidelines and asthma control test (ACT). Sputum eosinophil percentages and exhaled nitric oxide (eNO) were measured as markers of airway inflammation. Peripheral blood eosinophils count, anti-neutrophil cytoplasmic autoantibody (ANCA), eosinophil cationic protein (ECP), IgE, IL2, IL4 and IL5 were also assessed.Two-dimensional electrophoresis (2DE) was employed to characterize the salivary proteomic profiles of the subjects enrolled in the study. Western Blot analysis with an anti-cystatin C polyclonal antibody (Millipore) was performed to validate 2DE results. Results: Twenty one CSS patients (12 M:9F; mean age=57±12 yrs; mean follow up =7.6±4.8 yrs) and 10 sex and age matched healthy volunteers were enrolled in the study. Eight patients out of 21 showed a positivity for ANCA. At study entry, all the patients were on clinical remission and on maintenance therapy with low steroids and methotrexate. None of the patients had current or previous renal involvement. Asthma was poorly controlled in 17/21 patients. Both 2DE results and WB analysis showed that Cystatin C was significantly reduced in CSS patients with respect to healthy volunteers (p-value=0.03). Similarly Cystatin S (p=0.04) and Cystatin SA (p=0.03) but not Cystatin SN were reduced in the patient group with respect to healthy volunteers. Salivary Cystatin C levels did not correlate with asthma severity as assessed by clinical, physiologic and blood measurements. Conclusions: This preliminary study demonstrated a peculiar pattern in the proteolytic profile of cysteine proteases and their inhibitors in CSS patients with respect to healthy volunteers. Additional studies are required in order to clarify whether the apparent decrease of Cystatin C has a pathogenetic role in CSS or it might be considered as an epiphenomenon of the concomitant asthma. Disclosure of Interest: None Declared